SOME FEATURES OF IMMUNE REGULATION IN PATIENTS WITH FIBROUS/CAVERNOUS PULMONARY TUBERCULOSIS - E. G. Churina; V. V. Novitskiy; O. I. Urazova; A. E. Kolosova; O. V. Voronkova; O. V. Filinjuk; E. V. Nekrasov; I. E. Yesimova; R. R. Khasanova (Медицинская иммунология, 2014)
Abstract. The study dealt with subpopulation analysis of peripheral blood T-regulatory cells (Treg), and in  vitro  testing  of  immunosuppressive  cytokine  (IL-10,  TGF-β)  production  in  the  patients  with  fibrous/cavernous pulmonary tuberculosis, depending on results of intracutaneous tuberculin tests (Mantoux test). We  have  shown  that  Trn,  natural  T-regulatory  lymphocytes  (CD4+CD25+FoxP3+),  and  TGF-β  cytokine, produced by these cells, play a leading role for immune suppression developing in fibrosis-cavernous pulmonary tuberculosis. Moreover, an imbalance of Treg cell subsets has been revealed in patients with fibrous/ cavernous pulmonary tuberculosis, with either positive, or negative Mantoux reaction, as shown by increased content of Treg cells with CD4+CD25+FoxP3+ phenotype, along with higher amounts of CD4+CD25-FoxP3+ subpopulations, and deficiency of CD4+CD25+FoxP3- Treg lymphocytes in blood samples (in cases of positive Mantoux tests). Increased amounts of CD4+CD25+FoxP3+ Treg cells in peripheral blood of patients with fibrous/cavernous pulmonary  tuberculosis  is  associated  with  increase  in  basal  and  BCG-induced  TGF-β  production,  and decreased in vitro IL-10 secretory potential. (Med. Immunol., 2011, vol. 13, N 2-3, pp 267-272)